Deep vein thrombosis - the review - Karol Stępniak; Wiktor Telega; Kinga Wnuczek; Joanna Wrona; Aleksandra Kaźmierczyk; Jędrzej Kęsik; Daria Madycka; Kacper Michta; Małgorzata Słaboń; Maciej Sobczyk (Nicolaus Copernicus University in Toruń, 2024)
Deep vein thrombosis impacts between 2.5% and 5% of a population. It mostly affects lower-extremity veins and presents itself as pain, swelling, tenderness, and erythema of an affected region. Thrombus forms when at least one factor from the Virchow's triad is present - vascular damage, venous stasis or hypercoagulability. A range of clinical manifestations is very wide, from asymptomatic to life-threatening course of the disease. Post-thrombotic syndrome is a frequent complication that results in venous hypertension, which leads to tissue edema, subcutaneous fibrosis, and subsequent ulceration. In the diagnostic process, predominantly D-dimer assay and ultrasonographic compression test are performed. Noninvasive treatment relies on anticoagulation therapy which is based on direct oral anticoagulants, parenteral anticoagulants, and vitamin K antagonists. In specific cases, there is an option of invasive treatment, which involves inserting a catheter into a vein with a thrombus. Afterward, a thrombus can be mechanically fragmented and aspired or dissolved with the use of a thrombolytic agent.